Creative undisciplining: Report on the 6th International Conference on Community Psychology, Durban, South Africa, 27-30 May 2016 - Malherbe, Nick; Helman, Rebecca; Cornell, Josephine (PINS-Psychology in Society, 2024)
You may write me down in history With your bitter, twisted lies, You may trod me in the very dirt But still, like dust, I’ll rise. – Maya Angelou, Still I rise So don’t you forget (no way) your youth, Who you are and where you stand in struggle – Bob Marley, So much things to say An open letter to Bob Marley, which called for a re-animation of a decolonial, humanising psychic revolt – the echo of Thabo Mbeki’s iconic I am an African speech – a screening of Maya Angelou’s rendition of her rousing poem, Still I Rise; a night of song and dance; a visual display of protest against the Brazilian coup d’état; and unrestrained emotion in response to stirring human rights documentary films were just a few of the events that made the 6th International Conference on Community Psychology (ICCP2016) a site of “creative undisciplining”. This term, which Professor Nelson Maldonado-Torres used in his keynote address to refer to the student protests that have been occurring around the world in response to colonial, and neoliberal inequalities, appears an apt description for this conference, which opened up a space for critical interrogation of the discipline of community psychology in varied and creative ways.